2021
DOI: 10.3390/children9010024
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Current State of Evidence of the Incredible Years Teacher-Classroom Management Program

Abstract: This meta-analysis evaluated the current state of evidence and identified potential treatment moderators of the Incredible Years Teacher Classroom Management (IYTCM) program used to reduce externalizing and internalizing behaviors in school-aged children. Inclusion criteria involved published studies between 1984–2018 and examining the effects of IYTCM as a standalone program on teacher and/or child behavioral outcomes. We identified and narratively summarized potential moderators, which included the severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
8
0
2
Order By: Relevance
“…This review will provide the field with a comprehensive dataset of classroom management measures used in the school-based literature, to provide a summary evaluation and descriptors of these assessments. Although there have been numerous syntheses of intervention research of both group and single-case designs (e.g., Bowman-Perrott et al, 2016; Chaffee et al, 2017; Kaya & Selvitopu, 2019; Korest & Carlson, 2021; Korpershoek et al, 2016; Long et al, 2019; Maggin et al, 2017), the extent that these reviews capture and evaluate assessments of classroom management over and above implementing an intervention is unknown. This review specifically aims to synthesize this research base with the intention of identifying and reviewing measures or assessments of classroom management .…”
Section: Classroom Management Measuresmentioning
confidence: 99%
“…This review will provide the field with a comprehensive dataset of classroom management measures used in the school-based literature, to provide a summary evaluation and descriptors of these assessments. Although there have been numerous syntheses of intervention research of both group and single-case designs (e.g., Bowman-Perrott et al, 2016; Chaffee et al, 2017; Kaya & Selvitopu, 2019; Korest & Carlson, 2021; Korpershoek et al, 2016; Long et al, 2019; Maggin et al, 2017), the extent that these reviews capture and evaluate assessments of classroom management over and above implementing an intervention is unknown. This review specifically aims to synthesize this research base with the intention of identifying and reviewing measures or assessments of classroom management .…”
Section: Classroom Management Measuresmentioning
confidence: 99%
“…efficacité à modifier à la fois les stratégies de gestion des comportements et les problèmes de comportement des élèves (Daley et al, 2014;Oliver et Reschly, 2014), la mise sur pied de programmes de formation continue pour les enseignants représente une piste à continuer d'explorer et à promouvoir. Plusieurs formations en gestion des problèmes de comportement ont aussi montré leur capacité à améliorer à la fois les stratégies mobilisées par les enseignants, mais aussi le comportement des élèves (Korest et Carlson, 2022;Maini, 2011;Stoiber et Gettinger, 2011).…”
Section: Les Limites De L'étudeunclassified
“…For example, Carlson et al (2011) reported eight 4 h sessions over an 8–10 weeks period for a total of 32 h of training, and Gaspar et al (2022) reported six 6 h workshops once a month or every 3 weeks, interspersed with 2 hours individual in loco peer coaching. According to Korest and Carlson (2022) , dosage should be calculated not considering the number of sessions, because of the varied number of sessions offered, but rather by the number of hours, coding as “high dosage” if the training offered lasts at least 42 h.…”
Section: Introductionmentioning
confidence: 99%
“…In different countries, the IY-TCM as a stand-alone school-based intervention showed promising benefits for both children and teachers. Results from a very recent meta-analysis—one designed both to assess the current state of evidence in improving teachers’ and children’s outcomes and to identify potential intervention moderators of the effects of the IY-TCM as a stand-alone program ( Korest and Carlson, 2022 )—revealed the program had moderate positive effects on teachers (use of positive and negative IY-TCM classroom management strategies) with larger effect sizes in higher dosage studies (training hours offered greater than or equal to 42 h). Considering the effects on children, the results indicated small positive effects on children’s externalizing behavior and prosocial skills for teacher-rated reports, with larger effect sizes for higher risk children (behavioral problems above the clinical range defined by the study).…”
Section: Introductionmentioning
confidence: 99%